1998
DOI: 10.1210/endo.139.3.5855
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Calcitonin-Like Peptides from Rat Brain and Pituitary*

Abstract: Accumulating evidence supports the existence of nonthyroidal calcitonin (CT)-like peptides, more similar to fish CTs, which may act as endogenous regulators of CT receptors in brain and other tissues. In this study, we have carried out large-scale extractions from SpragueDawley rat brain diencephalon and pituitary, and purified a novel, biologically active, CT-like peptide from pituitary. Monitoring of the calcitonin-like activity of the peptides from rat brain and pituitary required different detection system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The primary structures of calcitonins from a number of species are known, and these show variations in amino acid sequence throughout most of their length. 4 Nevertheless, a number of structural features are conserved that appear to be important determinants of receptor recognition and function. These include a highly conserved N-terminal disulfide loop linking cysteine residues in positions 1 and 7, a potential amphiphilic R-helical structure in residues 8 through 22, 5 and a C-terminal amide.…”
Section: Introductionmentioning
confidence: 99%
“…The primary structures of calcitonins from a number of species are known, and these show variations in amino acid sequence throughout most of their length. 4 Nevertheless, a number of structural features are conserved that appear to be important determinants of receptor recognition and function. These include a highly conserved N-terminal disulfide loop linking cysteine residues in positions 1 and 7, a potential amphiphilic R-helical structure in residues 8 through 22, 5 and a C-terminal amide.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have demonstrated that CT is biosynthesized and secreted by gonadotrophs in the anterior pituitary gland [15,21]. In addition, there are also reports of the presence of SCT-like immunoreactive peptide in the mammalian pituitaries including rodents and humans [15,38,39]. Moreover, both SCT and HCT (or rat CT) have been shown to interact with the same CTR, and SCT is generally found to be more potent than HCT in most biological assays [40][41][42][43].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the mRNA of the C1b subtype was not detected in either mouse pituitary or TtT/GF cells. C1b is considered to be a receptor for endogenous sCT-like peptides (47)(48)(49). The physiological plasma level of CT in rats is approximately 60 pg/ml (0.02 nm) to 480 pg/ml (0.1 nm) (50).…”
Section: Discussionmentioning
confidence: 99%